Top-Down and Bottom-Up Modulation of Pain-Induced Oscillations - Hauck, Michael; Lorenz, Jürgen; Domnick, Claudia; Gerloff, Christian; Engel, Andreas K. (Frontiers in Human Neuroscience, 2015)
Attention is an important factor that is able to strongly modulate the experience of pain. In order to differentiate cortical mechanisms underlying subject-driven (i.e. top-down) and stimulus-driven (bottom-up) modes of attentional pain modulation, we recorded electric brain activity in healthy volunteers during painful laser stimulation while spatial attention and stimulus intensity were systematically varied. The subjects’ task was to evaluate the pain intensity at the attended finger, while ignoring laser stimuli delivered to the other finger. Different time-frequency signatures of the EEG data were modulated by top-down (attention) and bottom up (intensity) processes. Attention towards pain induced a decrease in alpha and an increase in gamma band power, localized in the insula, whereas pain intensity modulated delta, alpha, beta and gamma power. Source localization revealed stimulus driven modulation in the cingulate gyrus and somatosensory areas for gamma power changes. Our results indicate that bottom-up and top-down modes of attention exert different effects on pain-induced slow and fast oscillatory activities. Future studies may examine oscillations using this paradigm to test for altered attentional pain control in patients with chronic pain.